High-performance glass fiber composition and preparation method thereof

By adopting a combination of multiple oxides with high ionic field strength and low polarization in glass fibers and controlling component ratios, the problem of insufficient dielectric and mechanical properties of existing glass fibers is solved, and a combination of high elastic modulus, low dielectric constant and loss is achieved.

CN119797757APending Publication Date: 2025-04-11NANJING FIBERGLASS RES & DESIGN INST CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411955178.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing glass fibers have high dielectric constant and losses under high frequency conditions, making it difficult to meet the rigidity design requirements of composite materials, and at the same time, their mechanical properties are insufficient.

Method used

A high performance glass fiber composition is prepared, including SiO2, B2O3, Al2O3, MgO, CaO, ZnO, ZrO2, TiO2, F2 and P2O5 components, and other components are combined, and the proportion and addition amount of each component are controlled.

Benefits of technology

Without increasing the dielectric constant and dielectric loss, the elastic modulus of glass fiber is increased so that its dielectric constant is not greater than 4.75, the dielectric loss is not greater than 0.0035, and the elastic modulus of glass is not less than 75GPa, while ensuring the process performance of glass fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215617850000111
    Figure BDA0005215617850000111
  • Figure BDA0005215617850000121
    Figure BDA0005215617850000121
  • Figure BDA0005215617850000131
    Figure BDA0005215617850000131
Patent Text Reader

Abstract

The invention provides a high-performance glass fiber composition and a method for preparing glass fiber by using the high-performance glass fiber composition, and the high-performance glass fiber composition comprises the following components in molar percentage: 61 to 67 percent of SiO2, 7.0 to 16.0 percent of B2O3, 0.1 to 16.0 percent of Al2O3, 3.0 to 12.5 percent of MgO, 0.02 to 9.0 percent of CaO, 0.01 to 5.0 percent of ZnO, 0.1 to 5.0 percent of ZrO2, 0.1 to 4.0 percent of TiO2, 0 to 3.0 percent of F2 and 0 to 4.0 percent of P2O5. Wherein F2 and P2O5 are not 0 at the same time. According to the invention, a plurality of specific component oxides with high ion field intensity and low polarizability are combined, and the proportion and addition amount of each component are controlled, so that the elastic modulus of the glass fiber is improved under the condition that the dielectric constant and dielectric loss are not improved, and the processing property of the glass fiber is ensured; the dielectric constant of the glass fiber is not more than 4.75, the dielectric loss is not more than 0.0035, and the elasticity modulus of the glass is not less than 75 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fiber preparation, and in particular to a high-performance glass fiber composition and a method for preparing glass fiber using the same. Background Art

[0002] Glass fiber has good electrical insulation and electromagnetic transparency. As a composite material reinforcement, it should have good mechanical properties to meet the composite material stiffness design requirements. Thin-walled radomes and printed circuit board substrates for high-frequency wave transmission require glass fiber to have low dielectric constant and loss, as well as certain strength and modulus.

[0003] At present, the wave-transparent cover or substrate is usually made of alkali-free (E), low dielectric (D), high strength (S) and quartz (Q) glass fibers. Among them, the S glass fiber (silicon aluminum magnesium oxide system) has the highest mechanical properties, and the glass elastic modulus reaches 92GPa, but its dielectric constant and loss are relatively high. Under 10GHz test conditions, the S-2 glass has a dielectric constant of 5.2, a dielectric loss of 0.0068, and an elastic modulus of 92GPa; the low dielectric glass fiber (silicon boron aluminum oxide system) has a dielectric constant and loss of 2.37 and 1.33, respectively. The dielectric constant and loss of E glass fiber are 4.8 and 0.0035, but the elastic modulus of glass is less than 70 GPa. The E glass fiber (silicon alkaline earth aluminum boron oxide system), which is currently used in large quantities, has a tensile modulus of 78 GPa for its fiber dipped yarn, but its dielectric constant and loss are relatively high, which are 6.2 and 0.0039 respectively. The dielectric properties of quartz glass fiber (SiO2>99.98%) are the best among all glass fibers, with a dielectric constant and loss of 4.0 and 0.002 respectively, and an elastic modulus of 76 GPa, but the price of quartz fiber is high.

[0004] Based on this, there is an urgent need to provide a high-performance glass fiber composition and a method for preparing glass fiber using the same. Summary of the invention

[0005] The embodiments of the present invention provide a high-performance glass fiber composition and a method for preparing glass fiber using the same, which can provide a multi-component glass fiber having excellent mechanical properties and dielectric properties and good production operability, and is suitable for large-scale production.

[0006] In a first aspect, the present invention provides a high-performance glass fiber composition, which comprises the following components, in molar percentage: SiO2: 61-67%, B2O3: 7.0-16.0%, Al2O3: 0.1-16.0%, MgO: 3.0-12.5%, CaO: 0.02-9.0%, ZnO: 0-5.0%, ZrO2: 0.1-5.0%, TiO2: 0.1-4.0%, F 2:0~3.0%、P2O5:0~4.0%;Among them, ZnO、F 2 It is 0 when it is different from P2O5.

[0007] Preferably, the high performance glass fiber composition further comprises the following components, measured in mole percentage: BaO: 0.01-4.0%, SrO: 0.01-5.0%.

[0008] Preferably, the high-performance glass fiber composition further comprises the following components, measured in molar percentage: LiO2: 0.01-3%, Y2O3: 0.01-0.8%.

[0009] Preferably, M1=SiO2+B2O3, wherein, in molar percentage, 73%≤M1≤80%.

[0010] Preferably, M2=MgO+CaO+BaO+SrO, wherein, in molar percentage, 8.0%≤M2≤16.0%.

[0011] Preferably, in molar percentage, the ratio of the content of B2O3 to M2 is 0.5 to 2.0.

[0012] Preferably, M3=(Al2O3+M2) / M1, wherein, in molar percentage, 0.1%≤M3≤0.4%.

[0013] Preferably, M4=ZrO2+Y2O3+TiO2, wherein, in molar percentage, 0.3%≤M4≤7.5%.

[0014] Preferably, M5=P2O5+F 2 , wherein, in mole percentage, 0.7%≤M5≤7.0%.

[0015] Preferably, the high-performance glass fiber composition includes the following components, in molar percentage: SiO2: 54-65.5%, B2O3: 8.0-16.0%, Al2O3: 0.1-10.5%, MgO: 3.0-12.0%, CaO: 0.05-8.5%, ZnO: 0.01%-3.8%, ZrO2: 0.5-4.5%, TiO2: 0.3-3.5%, F2: 0.5-4.0%, P2O5: 0.05-3.0%, BaO: 0.01-3.5%, SrO: 0.01-3.4%, LiO2: 0.01-2.0%, Y2O3: 0.01-0.75%.

[0016] In a second aspect, the present invention provides a method for preparing high-performance glass fiber from the high-performance glass fiber composition according to any one of the first aspects, the method comprising the following steps:

[0017] (1) stirring and mixing each component according to mole percentage to obtain a high-performance glass fiber composition;

[0018] (2) melting the high-performance glass fiber composition to obtain homogeneous glass;

[0019] (3) Drawing the homogeneous glass to obtain the high-performance glass fiber.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects:

[0021] In the present invention, a plurality of specific component oxides with high ion field strength and low polarizability are combined, and the proportion and addition amount of each component are controlled. In this way, the elastic modulus of the glass fiber is improved without increasing the dielectric constant and dielectric loss, and the process performance of the glass fiber is guaranteed. Experiments show that the dielectric constant of the glass fiber is not greater than 4.75, the dielectric loss is not greater than 0.0035, and the glass elastic modulus is not less than 75 GPa. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] The embodiment of the present invention provides a high-performance glass fiber composition, which includes the following components in molar percentage: SiO2: 61-67% (for example, 61%, 62%, 63%, 64%, 65%, 66% or 67%), B2O3: 7.0-16.0% (for example, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 16%), Al2 O3: 0.1-16.0% (for example, 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0% or 16.0%), MgO: 3.0-12.5% ​​(for example, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0% or 16.0%), 0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0% or 12.5%), CaO: 0.02% to 9.0% (for example, 0.02%, 0.05%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%), ZnO: 0.01% to 5.0% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0% or 5.0%), ZrO2: 0.1-5.0% (for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%), TiO2: 0.1-4.0% (for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%), F 2 : 0-3.0% (for example, 0, 0.01%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%), P2O5: 0-4.0% (for example, 0, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%); wherein, F 2 It is 0 when it is different from P2O5.

[0024] In an embodiment of the present invention, a plurality of specific component oxides with high ion field strength and low polarizability are combined, and the proportion and addition amount of each component are controlled. In this way, the elastic modulus of the glass fiber is improved without increasing the dielectric constant and dielectric loss, and the process performance of the glass fiber is guaranteed. Experiments have shown that the dielectric constant of the glass fiber is not greater than 4.75, the dielectric loss is not greater than 0.0035, and the glass elastic modulus is not less than 75 GPa.

[0025] At the same time, in the embodiment of the present invention, SiO2 and B2O3 are used as the main components of the glass, and SiO2 can serve as a network former of the glass structure. On the one hand, part of B2O3 can form a [BO4] tetrahedral structure and enter the glass silicon oxygen network structure, thereby playing a role in network reinforcement. On the other hand, B2O3 can effectively inhibit ion polarization and thus reduce the dielectric constant and dielectric loss of the glass fiber. By adding specific types of oxides with high ion field strength and low polarizability such as Al2O3, MgO, CaO, ZnO, ZrO2, TiO2, F 2 Like P2O5, ZrO2 and TiO2 are network exosomes in the glass structure. ZrO2 can increase the high-temperature viscosity of the glass, improve the glass density and elastic modulus. The polarizability of ZrO2 is lower than that of Al2O3. Adding it to the glass can help further reduce the dielectric constant and loss of the glass fiber. At the same time, a certain content of TiO2 can increase the density and modulus of the glass fiber, and the increase in the dielectric constant of the glass fiber is relatively slow compared to alkaline earth oxides. However, excessive content of TiO2 and ZrO2 will not only increase the cost, but also make the viscosity of the glass too high, thereby reducing the processing performance of the glass. Although Zn 2+ The mass is greater than that of Mg2+ and Ca 2 + However, since its outer layer has 18 electrons, its electron binding energy is high and the electron displacement polarization is small, it is beneficial to further reduce the dielectric constant and dielectric loss of glass fiber. In addition, it is found in the embodiment of the present invention that when Mg 2+ , Ca 2+ and Zn 2+ When they are compounded and introduced into glass, they will produce a synergistic effect to further reduce the dielectric constant and dielectric loss of glass fiber. When there are enough ions in the glass, the Al in Al2O3 3+ It can enter the glass network structure as [AlO4] tetrahedron, which can enhance the densification of the glass network structure, reduce the phase separation tendency of the glass, inhibit the formation of crystal nuclei to improve the forming process performance of the fiber, and improve the mechanical properties, dielectric properties and chemical corrosion resistance of the glass fiber. However, excessive Al2O3 introduction will not only lead to the appearance of a large number of network exosomes, resulting in excessively high melting temperature of the glass and enhanced crystallization tendency, but also lead to problems such as increased dielectric constant and dielectric loss of the glass fiber.

[0026] In the embodiment of the present invention, through the coordinated control of each component, it is not only beneficial to enhance the processing performance of the glass, so that the glass fiber has good drawing stability, but also the elastic modulus of the glass can be improved without increasing the dielectric constant and dielectric loss, so that the prepared glass fiber has both excellent dielectric properties and mechanical properties.

[0027] According to some preferred embodiments, the high performance glass fiber composition further includes the following components, measured in mole percentage: BaO: 0.01-4.0% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%), SrO: 0.01-5.0% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 4% or 5.0%).

[0028] In the present invention, the inventors found that increasing Mg 2+ , Ca 2+ , Ba 2+ , Sr 2+ The content of alkaline earth metal oxides will make the dielectric constant, ion polarizability and dielectric constant of glass fiber increase. However, when multiple alkaline earth ions exist, due to the presence of a blocking effect similar to the mixed alkali effect, ion vibration or relaxation will be hindered, and dielectric loss increases and slows down and is in a downward trend. Therefore, in the embodiment of the present invention, by further adding BaO and SrO on the basis of CaO and MgO, multiple alkaline earth metal oxides are formed, and then not only conducive to further reducing the dielectric constant of glass fiber, but also can improve the elastic modulus of glass fiber. And, the inventor further found that the increase of alkaline earth metal oxides is conducive to increasing the elastic modulus of glass fiber, and MgO is more significant on the impact of elastic modulus, therefore, in alkaline earth metal oxides, the molar percentage of controlling MgO is greater than the molar percentage sum of other three kinds of alkaline earth metal oxides, which is conducive to ensuring that the dielectric loss and dielectric constant of glass fiber are lower, ensuring that the elastic modulus and process performance of glass fiber are better.

[0029] According to some preferred embodiments, the high performance glass fiber composition further includes the following components, measured in molar percentage: LiO2: 0.01-3% (for example, 0.01%, 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0% or 3%), Y2O3: 0.01-0.8% (for example, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%).

[0030] In the embodiment of the present invention, the high-performance glass fiber composition also includes a certain content of LiO2 and Y2O3. Li2O can reduce the melting temperature of glass and the forming temperature of fiber, and improve the thermal stability of glass. At the same time, Li2O can be used as a flux to reduce the melting temperature of glass, improve production efficiency, and help to form the desired glass structure. Further, the addition of an appropriate content of Li2O can further reduce the dielectric constant of glass and provide dielectric properties of glass. At the same time, the addition of Y2O3 can aggregate non-bridging oxygen in Si-O bonds, making the network structure more compact. At the same time, an appropriate content of Y2O3 can also help to reduce the dielectric constant and dielectric loss of glass fiber. Too high an introduction not only increases the cost, but also reduces the effect on optimizing the dielectric properties of glass.

[0031] According to some preferred embodiments, M1=SiO2+B2O3, wherein, in molar percentage, 73%≤M1≤80%.

[0032] In the embodiment of the present invention, considering that SiO2 can form a network-forming body of glass structure with silicon-oxygen tetrahedron, the network-forming body has strong mechanical strength, and the formed network structure has high bond strength, is not easy to polarize under the action of external electric field, and has small losses such as conduction and relaxation at high frequency, so increasing the content of SiO2 can reduce the dielectric constant and dielectric loss of glass fiber. If the content of SiO2 is too high, the viscosity of glass will be too large, glass melting and fiber forming will be difficult, and the network space volume will be large and easy to deform, so that the elastic modulus of glass will be reduced.

[0033] A certain content of B2O3 can reduce the liquidus temperature of glass and help to increase the temperature range of glass fiber forming. When there is enough free oxygen, part of B2O3 forms a [BO4] tetrahedral structure and enters the glass silicon oxygen network structure, thereby playing a role in network reinforcement. At the same time, on the one hand, the BO bond energy is larger than the Si-O bond energy, which can effectively inhibit ion polarization in the glass structure and thus reduce the dielectric constant and dielectric loss of glass fiber; on the other hand, the presence of B2O3 makes more B 3+ It exists in the form of [BO3] triangles, forming a layered structure. This structure has weak coupling, which can reduce the high-temperature viscosity of the glass and is beneficial to the melting and clarification of the glass. However, the addition of B2O3 can reduce the rigidity of the glass network, thereby reducing the elastic modulus of the glass, so the content of B2O3 needs to be precisely controlled.

[0034] Further, it is found through experimental verification that the dielectric constant of glass fiber is mainly affected by the total polarizability of ions and the number of ions per unit volume. Usually, the dielectric constant increases with the increase of the total polarizability of positive and negative ions in the glass, and decreases with the increase of molar volume. While SiO2 and B2O3 have lower polarizability and higher molar volume, increasing SiO2 and B2O3 helps to reduce the dielectric constant of glass, but the elastic modulus of glass increases with the increase of ionic field strength and the increase of molar volume, showing an opposite trend to the dielectric constant. Therefore, in the embodiment of the present invention, the molar percentage sum of SiO2 and B2O3 is controlled within a reasonable range, which is conducive to balancing the dielectric properties and mechanical properties of glass fiber on the basis of ensuring the better processability of glass fiber.

[0035] According to some preferred embodiments, M2=MgO+CaO+BaO+SrO, wherein, in mole percentage, 8.0%≤M2≤16.0%.

[0036] In the embodiment of the present invention, the addition of alkaline earth metal oxides is beneficial to improving the dielectric constant and ion polarizability of the glass fiber, thereby improving the dielectric constant. However, when multiple alkaline earth ions are present, due to the existence of a blocking effect similar to the mixed alkali effect, the vibration or relaxation of the ions will be hindered, the increase in dielectric loss will slow down and show a downward trend, and the increase of multiple alkaline earth oxides is beneficial to increasing the elastic modulus of the glass, but too high an alkaline earth oxide content will be unfavorable for reducing the dielectric constant. Therefore, in the embodiment of the present invention, by controlling the total amount of alkaline earth metals, it is beneficial to ensure that the glass fiber has both good dielectric properties and elastic modulus.

[0037] According to some preferred embodiments, the ratio of the content of B2O3 to M2 is 0.5 to 2.0 in mole percentage.

[0038] In the embodiment of the present invention, a certain content of B2O3 can reduce the liquidus temperature of the glass, which helps to increase the forming temperature range of the glass fiber. When there is enough free oxygen, part of the B2O3 forms a [BO4] tetrahedral structure and enters the glass silicon oxygen network structure, thereby playing a role in network reinforcement. In addition, the BO bond energy is larger than the Si-O bond energy, which can effectively inhibit ion polarization in the glass structure and thus reduce the dielectric constant and dielectric loss of the glass fiber. However, excessive B2O3 content will cause the elastic modulus of the glass to decrease, so the ratio of the B2O3 content to M2 is adjusted to 0.5 to 2.0.

[0039] According to some preferred embodiments, M3=(Al2O3+M2) / M1, wherein, in molar percentage, 0.1%≤M3≤0.4%.

[0040] In the embodiment of the present invention, Al in Al2O3 3+[AlO4] tetrahedron can enter the glass network structure, which can enhance the densification of the glass network structure, reduce the phase separation tendency of the glass, inhibit the formation of crystal nuclei to improve the forming process performance of the fiber, and improve the mechanical properties, dielectric properties and chemical corrosion resistance of the glass fiber. However, excessive Al2O3 introduction will not only lead to the appearance of a large number of network exosomes, resulting in excessively high melting temperature of the glass, enhanced crystallization tendency, but also lead to problems such as increased dielectric constant and dielectric loss of the glass fiber. The addition of alkaline earth metal oxides is beneficial to improving the dielectric constant and ion polarizability of the glass fiber, thereby improving the dielectric constant. However, it is found in the embodiment of the present invention that when there are at least two alkaline earth metal oxides, the dielectric constant and dielectric loss of the glass fiber can be slowed down and show a downward trend. Therefore, in the embodiment of the present invention, appropriate amounts of BaO, SrO, CaO and MgO are added, which is beneficial to further reduce the dielectric loss and dielectric constant of the glass fiber. At the same time, magnesium oxide has a significant effect on the elastic modulus of glass, but excessive amounts will cause phase separation in the glass. Therefore, the value of (Al2O3+M2) / M1 needs to be adjusted to relatively increase the elastic modulus of the glass while ensuring low dielectric constant and loss.

[0041] According to some preferred embodiments, M4=ZrO2+Y2O3+TiO2, wherein, in molar percentage, 0.3%≤M4≤7.5%.

[0042] In the embodiment of the present invention, since TiO2, ZrO2 and Y2O3 are all network exosomes in the glass structure, after being added to the glass component, the elastic modulus of the glass structure can be enhanced in different ways, and the dielectric constant and dielectric loss of the glass fiber can be reduced. By controlling the total content of the three in molar percentage, it is beneficial to better regulate the elastic modulus and dielectric properties of the glass fiber while ensuring the good process performance of the glass fiber. However, if the content of the three is too high, it will not only increase the high temperature viscosity of the glass and reduce the process performance of the glass, but also reduce the effect on optimizing the dielectric properties of the glass.

[0043] According to some preferred embodiments, M5=P2O5+F 2 , wherein, in mole percentage, 0.7%≤M5≤7.0%.

[0044] In order to avoid the adverse effects of alkaline earth metal oxides and high-valent oxides on the dielectric properties of glass fibers, a certain amount of F is added to the glass component in the embodiment of the present invention. 2 (in the form of fluoride) and P2O5. - Ions can combine with cations to reduce the ionic radius and polarizability, which is beneficial to further reduce the dielectric constant and dielectric loss of glass fiber. + or Mg2+ Isocations and F - After combining, the polarizability is lower than that of these ions and O 2- The combined polarizability, lower polarizability is conducive to further ensuring the lower dielectric constant and loss of glass fiber, and fluoride can effectively reduce the high temperature viscosity of glass melt, thereby reducing the drawing temperature and improving the drawing process performance. The introduction of an appropriate content of P2O5 into silicate glass helps to reduce the number of non-bridging oxygen in silicate glass, aggregate the network structure, and help reduce the dielectric constant of glass. By further limiting the total content of the two, it helps to further ensure the better process performance and dielectric properties of glass fiber.

[0045] It should be noted that when SiO2, B2O3, P2O5, F 2 On the premise that MgO, CaO, BaO, SrO, ZrO2, and Y2O3 meet their respective ranges, the values ​​of M1, M3, M2, and M4 can be any value within the above-mentioned limited range.

[0046] According to some preferred embodiments, the high performance glass fiber composition comprises the following components in mole percentage:

[0047] SiO2: 61-65.5% (for example, 61%, 62%, 63%, 64%, 65% or 65.5%), B2O3: 8.0-16.0% (for example, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0% or 16.0%), Al2O3: 0.1-10.5% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10.5%), MgO: 3.0-12.0% (for example, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0% or 12.0%), CaO :0.05~8.5% (for example, it can be 0.02%, 0.05%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 8.5%), ZnO:0.01%~3.8% (for example, it can be 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 3.8%), ZrO2: 0.5-4.5% (for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0% or 4.5%), TiO2: 0.3-3.5% (for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0% or 3.5%), F 2:0.5~3.0% (for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%), P2O5:0.05~3.0% (for example, 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5% or 3.0%), BaO:0.01~3.5% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0% or 3.5%), SrO:0.01~3.5% (for example, 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0% or 3.5%), For example, it can be 0.01%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0% or 3.5%), LiO2: 0.01~2.0% (for example, it can be 0.01%, 0.05%, 0.1%, 0.5%, 1.0%, 1.5% or 2.0%), Y2O3: 0.01~0.75% (for example, it can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.75%).

[0048] In the embodiments of the present invention, through a large number of experimental screenings and data summarization, it is found that when a specific type of multi-component oxides with high ion field strength and low polarizability are used and their proportions and addition amounts are controlled, a suitable positive accumulation effect can be achieved, which is beneficial to enhancing the elastic modulus of the glass fiber without increasing the dielectric constant and dielectric loss, and the glass fiber drawing process is more stable and has excellent process performance.

[0049] It should be noted that the unavoidable impurities in the present invention are Na2O, K2O and Fe2O3 introduced from the raw materials, and the total content of such substances should be controlled within 0.3%.

[0050] The present invention also provides a method for preparing low dielectric glass fiber using the high performance glass fiber composition described in any one of the above, the method comprising the following steps:

[0051] (1) stirring and mixing each component according to mole percentage to obtain a high-performance glass fiber composition;

[0052] (2) melting the high-performance glass fiber composition to obtain homogeneous glass;

[0053] (3) Drawing the homogeneous glass to obtain the high-performance glass fiber.

[0054] In the embodiment of the present invention, the content of each component raw material is optimized and regulated to obtain the raw material of the low dielectric glass fiber. During the preparation process, the raw material can be melted into a glass state and then quenched with water, and then added to a platinum crucible for drawing, thereby preparing high-performance glass fiber. It should be noted that SnO2 or CeO2 can be used as a clarifier in glass melting, and the content of a single or combined clarifier is guaranteed not to exceed 0.5%.

[0055] The low dielectric glass fiber in the embodiment of the present invention has lower dielectric properties and higher elastic modulus. At 10 GHz, the dielectric loss of the glass fiber is not greater than 0.0035, the dielectric constant is not greater than 4.75, and the elastic modulus is not less than 75 GPa. In addition, the composition formed by the above components is easy to form glass fibers, and the forming window temperature is not less than 50°C.

[0056] It should be noted that, in the embodiments of the present invention, when melting, full oxygen combustion, full electric melting or a combination of fire and electricity can be used for kiln melting to form homogeneous glass. Furthermore, the kiln for melting glass can be a melting furnace composed of refractory materials that are resistant to high temperatures and erosion by glass liquid, such as electric fused high zirconium bricks, dense zirconium bricks, electric fused mullite bricks, etc. At the same time, a platinum-substituting furnace constructed of refractory dense zirconium bricks, corundum bricks, electric fused chromium zirconium corundum bricks, and mullite can be used for wire drawing production, that is, first using the high-performance glass fiber composition of the present invention to melt glass, and then using glass to draw glass fibers, or using the kiln passage constructed of the above-mentioned refractory materials for one-step wire drawing production.

[0057] The melting temperature and fiber forming temperature of the high-performance glass fiber composition components in the embodiments of the present invention are relatively high, and a melting furnace and a platinum-substituting furnace or a one-step tank furnace constructed of refractory materials that are resistant to high temperatures and erosion by molten glass are required for glass melting and fiber preparation.

[0058] An embodiment of the present invention further provides an application of any of the above-mentioned low-dielectric glass fiber high-frequency circuit boards.

[0059] The high-performance glass fiber prepared in the embodiment of the present invention can be used for wave-transmitting radar covers, and can also be used in the electronics industry to manufacture copper-clad laminates, printed circuit boards, etc. Due to the characteristics of low dielectric constant and low dielectric loss, it helps to improve the signal transmission speed and efficiency in high-speed data transmission and high-frequency circuit boards. In the field of aerospace, low-dielectric glass fiber can be used to manufacture lightweight and high-strength structural components. Low-dielectric glass fiber is an indispensable engineering material in the fields of high-level communications, aerospace, etc.

[0060] In order to more clearly illustrate the technical solution and advantages of the present invention, a high-performance glass fiber composition and a method for preparing glass fiber using the same are described in detail below through several embodiments.

[0061] According to the raw material composition of each formula listed in Table 1, the required mass percentage of various raw materials in Examples 1 to 13 and Comparative Examples 1 to 2 is calculated respectively, accurately weighed and evenly mixed to form the composition raw materials, pneumatically mixed and transported to the kiln charging port, and fed by an automatic feeder, and melted at about 1600°C in a full electric melting or thermal power combined kiln to obtain a clarified and homogenized glass liquid. The molten glass liquid is prepared into glass balls, and the molten glass balls are melted again at 1550°C, and a 400 or more bushing is used to control the glass fiber forming process parameters (liquid level, hot spot temperature, bushing temperature, drawing machine speed, etc.), and drawn into a continuous glass fiber with a diameter of 8 to 22 μm, and the fiber is tested for performance, and the results are shown in Table 1.

[0062] Table 1

[0063]

[0064]

[0065]

[0066] The glass density was tested using GB / T 5432 "Glass Density Determination Buoyancy Method". The liquidus temperature was determined using a gradient crystallization temperature test furnace, with reference to the standard ASTM C829. The sample was placed in a platinum boat and placed in a gradient furnace heated to 1400°C. The sample was kept warm for 2 hours, and then the crystallization position was observed. The crystallization upper limit temperature was calculated based on the temperature gradient. The high-temperature viscosity was determined using the American BROOKFIELD high-temperature viscometer, with reference to the standard (ASTM C965). Specifically, the sample was placed in a platinum crucible and placed in a furnace heated to 1500°C. The rotor was then immersed in the high-temperature glass liquid and kept warm for 1 hour. The high-temperature viscosity of the glass liquid was tested by the torque of the rotor. The elastic modulus was tested using the ultrasonic echo method with a glass block. The propagation rate of elastic waves in solid samples was measured. According to the propagation theory of elastic waves in solids, the propagation rate of different modes of sound waves in solids is related to the corresponding elastic modulus and density of the material, so as to calculate the elastic modulus of the glass fiber.

[0067] As can be seen from Table 1, the low dielectric glass fiber prepared by using the optimized raw material components and content combination in the present invention not only has good process performance, but also has a high elastic modulus and good dielectric properties.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-performance glass fiber composition, characterized in that: The high-performance glass fiber composition comprises the following components in molar percentage: SiO2: 61-67%, B2O3: 7.0-16.0%, Al2O3: 0.1-16.0%, MgO: 3.0-12.5%, CaO: 0.02-9.0%, ZnO: 0.01-5.0%, ZrO2: 0.1-5.0%, TiO2: 0.1-4.0%, F 2 :0~3.0%、P2O5:0~4.0%;Among them, F 2 It is 0 when it is different from P2O5.

2. The high performance glass fiber composition according to claim 1, characterized in that: In terms of molar percentage, the high-performance glass fiber composition further comprises the following components: BaO: 0.01-4.0%, SrO: 0.01-5.0%.

3. The high performance glass fiber composition according to claim 2, characterized in that: In terms of molar percentage, the high-performance glass fiber composition further comprises the following components: LiO2: 0.01-3%, Y2O3: 0.01-0.8%.

4. The high performance glass fiber composition according to claim 1, characterized in that: M1=SiO2+B2O3, wherein, in molar percentage, 73%≤M1≤80%.

5. The high performance glass fiber composition according to claim 2, characterized in that: M2=MgO+CaO+BaO+SrO, wherein, in mole percentage, 8.0%≤M2≤16.0%; and / or In terms of molar percentage, the ratio of B2O3 content to M2 is 0.5 to 2.

0.

6. The high performance glass fiber composition according to claim 5, characterized in that M3 =(Al2O3+M2) / M1, wherein, in molar percentage, 0.1%≤M3≤0.4%.

7. The high performance glass fiber composition according to claim 3, characterized in that: M4=ZrO2+Y2O3+TiO2, wherein, in molar percentage, 0.3%≤M4≤7.5%.

8. The high performance glass fiber composition according to claim 1, characterized in that: M5=P2O5+F 2 , wherein, in mole percentage, 0.7%≤M5≤7.0%.

9. The high performance glass fiber composition according to any one of claims 1 to 8, characterized in that: The high-performance glass fiber composition comprises the following components in molar percentage: SiO2: 54-65.5%, B2O3: 8.0-16.0%, Al2O3: 0.1-10.5%, MgO: 3.0-12.0%, CaO: 0.05-8.5%, ZnO: 0.01%-3.8%, ZrO2: 0.5-4.5%, TiO2: 0.3-3.5%, F 2 : 0.5~4.0%, P2O5: 0.05~3.0%, BaO: 0.01~3.5%, SrO: 0.01~3.4%, LiO2: 0.01~2.0%, Y2O3: 0.01~0.75%.

10. A method for preparing high-performance glass fiber according to the high-performance glass fiber composition according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: (1) stirring and mixing each component according to mole percentage to obtain a high-performance glass fiber composition; (2) melting the high-performance glass fiber composition to obtain homogeneous glass; (3) Drawing the homogeneous glass to obtain the high-performance glass fiber.

Citation Information

Cited By

  • Electronic-grade glass fiber composition, glass fiber cloth and preparation method thereof

    CN121248146A

  • Electronic-grade low-dielectric-loss glass fiber composition and composite material

    CN121779003A

  • High-performance glass fiber composition and preparation method therefor

    WO2026138164A1